Improving Students Speaking Ability Through Storytelling at Eleventh Grade of SMAN I Lambitu - Ika Irawati; Fitri Ningsi; Rahmi Rahmi; Ita Fitriati (Yayasan Pendidikan Bima Berilmu, 2022)
Speaking Ability was the important aspect in communication. The aim of the study was to investigate the improving speaking ability through storytelling in teaching speaking at eight grade of SMAN 1 Lambitu. This research used classroom action research. The subjects in this research were the students at the eleventh grade of SMAN 1 Lambitu. The sample were 16 students in one class. The researcher used the technique of storytelling through recount text to improve speaking skill. Quantitative data analysis technique used this research through average score and percentage of students’ test, while qualitative data analysis was taken from analysis of observation during the classroom. The result of this study was in cycle I was at fair category (60-70) which average score was 67,4. It indicated the students’ ability in storytelling was not active (<50%)., which the critical success 31,5%. While in cycle II, the result of students’ score was 75,3, which means that the students were good category (60-79). The result was indicated that the students habits in storytelling technique in cycle II was active (<80%). Moreover the result of observation were student enjoy the lesson and follow the teaching and learning process smoothly and regularly. So, the conclusion that story telling technique was improving students’ speaking ability at Eleventh Grade of SMA 1 Lambitu.